Stability and steady state analysis of control and safety systems of Nuclear Power Plants - Gupta, B.; Singh, P.; Singh, L. (Elsevier Ltd, 2020)
Control Systems are the first layer of safety in Nuclear Power Plants, the failure of which invokes Safety Systems. The failure of safety systems can lead to radiation exposure to the public. Therefore, it is essential to ensure the stability of such systems. This paper proposes an effective methodology for stability and steady state analysis of control and safety systems of Nuclear Power Plants. The methodology includes Petri net modeling and analysis of its dynamic behavior. Despite of its simplicity, it is very accurate. The application of the proposed techniques is shown and validated on a reactor protection system, which is under operation in six Nuclear Power Plants. © 2020 Elsevier Ltd
Keywords: Nuclear Power Plant; Petri net; Reactor protection system; System stability